Bacteria-Based Crack Healing of Nanosilica and Carbon Nanotube Modified Engineered Cementitious Composites - Tanyildizi, Harun; Bulut, Metehan; Ziada, Mahmoud (Asce-Amer Soc Civil Engineers, 2024)
This study investigated bacteria-based crack healing of nanosilica and carbon nanotube modified engineered cementitious composites (ECC). Nanosilica (NS) and carbon nanotubes (CNT) were used in ratios of 0%, 0.25%, 0.50%, and 0.75% of the cementitious materials by mass. NS and CNT modified ECC samples were produced and cured in plastic bags at 23 degrees C +/- 2 degrees C for 28 days. After 28 days, the microcracks were formed in the ECC specimens. Then, the healing procedure by a bacterial solution containing Sporosarcina pasteurii was applied to these samples. After this procedure, the splitting tensile strength, ultrasonic pulse velocity water permeability, and rapid chloride permeability were performed on the samples. Also, energy-dispersive X-ray (EDX), scanning electron microscopy (SEM), X-ray diffraction analysis (XRD), and Fourier Transform Infrared Spectroscopy (FTIR) analyses were used to examine the morphology of healing products. This study found that 0.75 NS-ECC had a higher healing ability than all samples, and the splitting tensile strength recovery rate of this sample was 131.46%.
Keywords: Engineered cementitious composites (ECC); Nanosilica (NS); Carbon nanotube (CNT); Bacteria-based crack healing; Mechanical properties